Engagement in HIV care and sexual transmission risk behavior among men who have sex with men using online social/sexual networking in Latin America. - Magidson, Jessica F; Biello, Katie B; Safren, Steven A; Rosenberger, Joshua G; Novak, David S; Mayer, Kenneth H; Mimiaga, Matthew J (AIDS care, 2015)
HIV/AIDS in Latin America is concentrated among men who have sex with men (MSM). However, accurate estimates of engagement in HIV care in this population can be difficult to ascertain because many do not self-identify as MSM. Given evidence of decreased HIV transmissibility in the context of antiretroviral therapy (ART) adherence, identifying individuals not in care who are engaging in HIV transmission risk behavior is crucial for secondary prevention. Primary aims of this study were to examine engagement in care from testing to ART adherence among MSM using online social/sexual networking across Latin America, and whether individuals not in care at each step reported greater sexual transmission risk behavior than those in care. In the overall sample (n = 28,779), approximately 75% reported ever being tested for HIV, and 9% reported having received an HIV diagnosis. Among known HIV-infected individuals, 20% reported not being in care, 30% reported not taking ART, and 55% reported less than 100% ART adherence. Over one-third of HIV-infected individuals reported sexual HIV transmission risk behavior, defined as unprotected anal intercourse (UAI) with a male partner of different/unknown HIV serostatus in the past three months. HIV-infected individuals not engaged in care more often reported UAI compared to those in care (OR = 1.29; 95% CI = 1.01-1.66). Although not statistically significant, HIV-infected individuals not on ART more often reported UAI compared to those on ART (OR = 1.18; 95% CI = 0.94-1.47). Individuals who reported less than 100% ART adherence more often reported UAI compared to individuals with 100% adherence (OR = 1.55; 95% CI = 1.26-1.90). Findings demonstrate that a substantial portion of HIV-infected MSM in Latin America who are likely not virologically suppressed from lack of ART use or adherence report sexual HIV transmission risk. Tailoring secondary HIV prevention for MSM in Latin America who are not in HIV care or adherent to ART may be warranted.